PEMBERDAYAAN KELOMPOK KADER KESEHATAN DESA TAMMANGALLE MELALUI PEMBUATAN VIRGIN COCONUT OIL (VCO) SALAH SATU ALTERNATIF PENCEGAHAN VIRUS COVID- 19 - Masniati Masniati; Erwin Erwin (Sambulu Gana : Jurnal Pengabdian Masyarakat, 2022)
There are several main problems faced by the partner group, namely (1) As a group member, you can make VCO, but the product often fails to harvest (2) The quality of the product made by the partner group is not clear and easily turns rancid. (3) This partner group has never received assistance in making VCO so that the group is powerless (4) Making VCO by new group members is carried out by themselves and has not developed management in the group. (5) Problems in the product marketing process, which is still one of the factors of entrepreneurship failure. This PKM activity is able to transfer knowledge, skills and mastery of technology to partner groups so that partner groups are able to explore the potential that exists in the environment to be efficient and innovate during the pandemic, and through the PKM program a business entrepreneur group of health cadres making VCO was born in Tammangalle Village